Use of Objective Psychomotor Tests in Health Professionals. Issue 3 (June 2014) - Causby, Ryan; Reed, Lloyd; McDonnell, Michelle; Hillier, Susan
Evaluation of psychomotor skills is undertaken in a number of broad contexts. This includes testing of health professional populations as a measure of innate ability, to evaluate skill acquisition, or to compare professions. However, the use of psychomotor tests is frequently confounded by a lack of understanding of a particular tool's psychometric properties, strengths, and weaknesses. To identify and appraise the most commonly used tests on health professional populations, 86 articles were reviewed and the top nine tests identified. Few tests have had sufficient validity or reliability testing on health professionals. Based on the evidence available, use of the Grooved Pegboard Test, the Purdue Pegboard Test, or the Finger Tapping Test is recommended for the evaluation of dexterity in a health professional population; however, this choice may be dependent on the task(s) to which findings are generalised. More rigorous evaluation of validity and other psychometric properties is required.